2015
DOI: 10.1007/s40262-015-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetics-Based Population Pharmacokinetics and Pharmacodynamics of Risperidone in a Psychiatric Cohort

Abstract: Background: There is a high inter-individual variability in risperidone and its active

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 66 publications
(90 reference statements)
0
35
0
Order By: Relevance
“…Similar to the previous study, there were no association of reported side effects (neurologic, cardiovascular, psychic, and sexual side effects) with CYP2D6 -predicted phenotype. Only minimum active moiety concentration was found to be associated with neurologic symptoms, especially the severity of tremor 90. However, one study showed a trend of the association between CYP2D6 PM phenotype and the presence of tardive dyskinesia (TD).…”
Section: The Consequence Of Cyp2d6 Polymorphisms In Risperidone-assocmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the previous study, there were no association of reported side effects (neurologic, cardiovascular, psychic, and sexual side effects) with CYP2D6 -predicted phenotype. Only minimum active moiety concentration was found to be associated with neurologic symptoms, especially the severity of tremor 90. However, one study showed a trend of the association between CYP2D6 PM phenotype and the presence of tardive dyskinesia (TD).…”
Section: The Consequence Of Cyp2d6 Polymorphisms In Risperidone-assocmentioning
confidence: 99%
“…Using a population pharmacokinetic approach is a strategy to find out a suitable risperidone dosage. Vandenberghe et al reported that CYP2D6 but not NR1/2 , POR , PPAR α, ABCB1 , CYP3A plays an important role in risperidone, 9-hydroxyrisperidone, and active moiety plasma concentration 90. However, the CYP2D6 metabolizer subpopulation into PM, EM, IM, UM should be analyzed.…”
Section: Challenges Opportunities and Future Directions In The Clinmentioning
confidence: 99%
“…The activity score system provided a more detailed classification for the subjects." 192 Genetics-Based Population Pharmacokinetics and Pharmacodynamics of Risperidone in a Psychiatric Cohort http://www.ncbi.nlm.nih.gov/pubmed/26129906 193 "High interindividual variability in plasma concentrations of risperidone and its active metabolite, 9hydroxyrisperidone, may lead to suboptimal drug concentration… Genetic polymorphisms of CYP2D6 play an important role in risperidone, 9-hydroxyrisperidone and active moiety plasma concentration variability, which were associated with common side effects. These results highlight the importance of a personalized dosage adjustment during risperidone treatment."…”
Section: Impact Of Cyp1a2 and Cyp2d6 Polymorphisms On Drug Metabolismmentioning
confidence: 99%
“…These results highlight the importance of a personalized dosage adjustment during risperidone treatment." 193…”
Section: Impact Of Cyp1a2 and Cyp2d6 Polymorphisms On Drug Metabolismmentioning
confidence: 99%
“…[2] Therapeutic plasma concentrations of risperidone and its active moiety are directly influenced by genetic variations in metabolic CYP 450 enzymes (CYP2D6 and slightly CY-P3A4/5) and transporter (ABCB1) enzymes, and are influenced by environment. Particularly drug interactions associated with intake of inducers or inhibitor may influence CYP or P-gp and alter the pharmacological profile of risperidone and its active metabolite, and their therapeutic effect [3,4]. The metabolic transformation of risperidone is determined by the genetic variations in CYP2D6 enzyme, and depending on the number of active copies of the gene patients are classified as extensive metabolizers (EM), intermediate metabolizers (IM), ultrarapid metabolizers (UM) and poor metabolizers (PM).…”
Section: Introductionmentioning
confidence: 99%